In-rich AlxIn1−xN grown by RF-sputtering on sapphire: from closely-packed columnar to high-surface quality compact layers. (11th January 2017) - Núñez-Cascajero, A; Valdueza-Felip, S; Monteagudo-Lerma, L; Monroy, E; Taylor-Shaw, E; Martin, R W; González-Herráez, M; Naranjo, F B
Abstract: The structural, morphological, electrical and optical properties of In-rich Al x In1− x N (0 < x < 0.39) layers grown by reactive radio-frequency (RF) sputtering on sapphire are investigated as a function of the deposition parameters. The RF power applied to the aluminum target (0 W–150 W) and substrate temperature (300 °C–550 °C) are varied. X-ray diffraction measurements reveal that all samples have a wurtzite crystallographic structure oriented with the c -axis along the growth direction. The aluminum composition is tuned by changing the power applied to the aluminum target while keeping the power applied to the indium target fixed at 40 W. When increasing the Al content from 0 to 0.39, the room-temperature optical band gap is observed to blue-shift from 1.76 eV to 2.0 eV, strongly influenced by the Burstein–Moss effect. Increasing the substrate temperature, results in an evolution of the morphology from closely-packed columnar to compact. For a substrate temperature of 500 °C and RF power for Al of 150 W, compact Al0.39 In0.61 N films with a smooth surface (root-mean-square surface roughness below 1 nm) are produced.